Simulating the Common Envelope Phase Using Moving-Mesh Hydrodynamics - (:unkn) unknown (My University, 2022)
Common envelope evolution (CEE) is a phase in the evolution of a binary system where a giant star and a smaller companion share a gaseous envelope, and is responsible for the formation of many systems of astrophysical interest. Despite its importance, CEE is not well understood due to the diverse physics involved. Astronomers have roughly modeled CEE using conserved quantities such as energy, but progress has been limited by uncertainties in the contributions of various energy sources. Thus, 3-D numerical simulations must be brought to bear. Here two methodologies are commonly employed, each of which comes with its own set of advantages: smoothed-particle hydrodynamics and Eulerian grid codes. A hybrid of these methods known as the moving-mesh code has been developed in an attempt to capture the best characteristics of each. We use the moving-mesh solver MANGA, which has recently been improved with the inclusion of physics modules relevant to CEE. We begin this work with an introduction to CEE in Chapter 1. We go through a step-by-step description of its four stages and summarize observations of transients that are thought to result from binary interactions. We then present an overview of simulation techniques in Chapter 2, showing how aspects of smoothed-particle hydrodynamics and Eulerian methods are implemented into moving-mesh schemes. We begin our numerical studies of CEE using MANGA in Chapter 3 and show that the ejection of the envelope is aided by the inclusion of hydrogen recombination and tidal forces. CEE simulations to date have neglected hydrodynamic interactions at the surface of the companion. As such, we discuss our development of moving boundary conditions in Chapter 4 and show how they can be used to model the companion object. We show that the orbital eccentricity is affected by the size of the companion through hydrodynamic torques. Finally, we describe our implementation of magnetohydrodynamics in Chapter 5. We find rapid amplification of a toroidal magnetic field at the onset of CEE, which is thought to assist in the formation of nebulae.
Keywords: Binaries; Hydrodynamics; Magnetohydrodynamics; Numerical methods